CONTRAST NASOPHARYNGEAL CT SCAN EXAMINATION PROSEDURE AT THE RADIOLOGY INSTALLATION AT ARIFIN ACHMAD HOSPITAL, RIAU PROVINCE. - Anisa Fitrah Ramadhani; Dini Febriyanti (Medical Imaging and Radiation Protection Research Journal, 2025)
Background: Contrast-enhanced Computed Tomography (CT) of the nasopharynx is an importantimaging modality for evaluating abnormalities of the nasopharyngeal region, including inflammatorylesions and tumors. Intravenous contrast media enhance visualization of soft tissue structures, vascularanatomy, lesion extent, and involvement of adjacent tissues, thereby improving diagnostic accuracy andtreatment planning. This study aimed to describe the procedure for contrast-enhanced CT examinationof the nasopharynx performed at the Radiology Department of RSUD Arifin Achmad, Riau Province.Methods: This study employed a qualitative descriptive design using a case study approach. Data werecollected through direct observation of the examination procedure, semi-structured interviews withradiographers and radiologists, and documentation review. The study was conducted at the RadiologyDepartment of RSUD Arifin Achmad, Riau Province. Data were analyzed descriptively by comparingthe clinical practice with the standard examination protocol.Results: The examination procedure included patient identification, assessment of renal functionthrough laboratory evaluation, informed consent, intravenous catheter placement, patient positioning,and contrast-enhanced scanning. Intravenous administration of 50 mL of Iopamiro contrast mediumusing a power injector was performed according to the hospital protocol. The examination successfullydemonstrated the nasopharyngeal anatomy, vascular structures, lesion boundaries, and the relationshipbetween the lesion and adjacent tissues. Compared with several literature references recommendingapproximately 25 mL of contrast medium, the hospital protocol utilized 50 mL to achieve optimalenhancement and diagnostic image quality.Conclusion: The contrast-enhanced CT examination of the nasopharynx at RSUD Arifin Achmadfollows a standardized procedure and provides optimal diagnostic information. The administration of50 mL intravenous contrast medium improves visualization of vascular structures, differentiates bloodvessels from tumor masses, and assists in assessing vascular displacement or tumor invasion, therebysupporting accurate diagnosis and appropriate treatment planning.